Energy in Africa Challenges and Opportunities - Hafner, Manfred (SpringerBriefs in Energy,, 2018)
This open access book presents a picture of the current energy challenges on the African continent (and the Sub-Saharan region in particular) and proposes pathways to an accelerated energy transition. Starting with an analysis of the status quo and the outlook for Africa's energy demand and energy access, it provides an account of the available resources, including hydrocarbons and renewable energy resources, which are playing an increasingly crucial role. It then moves on to analyze the level of investment required to scale-up Africa's energy systems, shedding light on the key barriers and elaborating on potential solutions. It also provides a suggestion for improving the effectiveness of EU-Africa cooperation. While mainly intended for policymakers and academics, this book also speaks to a broader audience interested in gaining an overview of the challenges and opportunities of the African energy sector today and in the future.